Distinct Transcriptional Programs Underlie Differences in Virulence of Isolates on Host Plants in a Fungal Pathogen, Colletotrichum gloeosporioides - Cheon, Wonsu; Kim, Young Soo; Balaraju, Kotnala; Lee, Younmi; Kwon, Hyeok Tae; Jeon, Junhyun; Jeon, Yongho (Frontiers in Microbiology, 2021)
Susceptible host plants challenged by fungal pathogens can display different types of lesions, which can be attributed to environmental factors affecting the nature of interactions between the host and pathogen. During our survey of apple anthracnose in Korea, two distinct types of disease symptoms, designated as progressive (PS) and static symptoms (SS), were recognized. PS is a typical, rapidly enlarging symptom of apple anthracnose, while SS is a small, dark speck that does not expand further until the harvesting season. Isolation and genotyping of pathogens from disease lesions suggested that all of them belong to Colletotrichum gloeosporioides, a well-known causal agent of apple anthracnose. Two types of isolates were comparable in growth on media, spore germination and appressorium formation, virulence test on fruits at various temperature conditions. Furthermore, they were analyzed at the molecular level by a phylogenetic tree, RNA-seq, and expression of virulence gene. However, the SS isolates were defective in appressorium-mediated penetration into the underlying substratum. RNA-seq analysis of PS and SS isolates showed that distinct transcriptional programs underlie the development of different types of anthracnose symptoms in host plants. One downregulated gene in SS encoded isocitrate lyase is essential for disease development via its involvement in the glyoxylate cycle. It partly explains why SS is less virulent than PS on host plants. Overall, our work challenges the traditional view on the development of different lesion types and provides valuable insights into variations that exist in the pathogen population.